Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/jssc.200700014
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous characterization of isoflavonoids and astragalosides in two Astragalus species by high‐performance liquid chromatography coupled with atmospheric pressure chemical ionization tandem mass spectrometry

Abstract: A method was developed for the simultaneous identification of astragalosides (AGs) and isoflavonoids (IFs) in the roots of Astragalus membranaceus and Astragalus mongholicus by HPLC coupled with atmospheric pressure chemical ionization MS/MS (HPLC-APCI-MS/MS). Diagnostic fragment ions of AGs and different group of IFs were obtained with one AG and eight IF standards analyzed by CID-MS, which were adopted as characteristic MS/MS fingerprints for further identification of these compounds in the two Astragalus sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 14 publications
5
40
0
1
Order By: Relevance
“…Additionally, 4, just like compound 1, had UV absorptions with maxima at 260 and 290 nm. Based on these data, the structure of 4 was proposed to be 6 00 -O-acetylcalycosin-7-O-b-D-glucopyranoside [5].…”
Section: Hplc-dad-esi-ms/ms Analysis Of 70%fmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, 4, just like compound 1, had UV absorptions with maxima at 260 and 290 nm. Based on these data, the structure of 4 was proposed to be 6 00 -O-acetylcalycosin-7-O-b-D-glucopyranoside [5].…”
Section: Hplc-dad-esi-ms/ms Analysis Of 70%fmentioning
confidence: 99%
“…By examining the known pterocarpane glucosides in Radix astragali, only 9,10-dimethoxypterocarpane-3-O-b-D-glucopyranoside and 3,9-dimethoxypterocarpane-10-O-b-D-glucopyranoside were found and are consistent with the above data. According to the content difference and the retention time in HPLC reported before [3][4][5][6][7][8][9][10], compounds 3 and 6 were therefore tentatively identified as 3,9-dimethoxypterocarpane-10-O-b-D-glucopyranoside and 9,10-dimethoxypterocarpane-3-O-b-D-glucopyranoside, respectively. Compound 4 exhibited a [M ?…”
Section: Hplc-dad-esi-ms/ms Analysis Of 70%fmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, multi-bioactive marker compounds are quite necessary and reasonable for the quality evaluation of the more complicated herbal prescription. Chemical investigations and pharmacological studies on BYHWD have revealed that the constituents of BYHWD are numerous and diverse, including flavonoids, monoterpene glycosides, saponins and organic acids (Sheng et al, 2005;Ma et al, 2002;Zhang et al, 2007;Yang et al, 2006;Dong et al, 2007). In order to evaluate this prescription effectively and comprehensively and to ensure its correct clinical application, the simultaneous quantification of these types of compounds is a reasonable and advisable approach to controlling the quality of BYHWD.…”
Section: Introductionmentioning
confidence: 98%